The last freedom religion from the public school to the public square - Viteritti, Joseph P., 1946- (Princeton : Princeton University Press, 2007)
The presidency of George W. Bush has polarized the church-state debate as never before. The Far Right has been emboldened to use religion to govern, while the Far Left has redoubled its efforts to evict religion from public life entirely. Fewer people on the Right seem to respect the church-state separation, and fewer people on the Left seem to respect religion itself--still less its free exercise in any situation that is not absolutely private. In The Last Freedom, Joseph Viteritti argues that there is a basic tension between religion and democracy because religion often rejects compromise as.
Fear and loathing -- Religion and public life -- Tennessee tales -- Why schools matter -- Politics, education, and religion -- Free exercise, vacated and denied -- Ageless wisdom -- American landscape -- Conscience and compromise.
Includes bibliographical references (p. [241]-262) and index.
Description based on print version record.
Keywords: Church and state -- United States; School choice -- United States; POLITICAL SCIENCE -- Political Process -- Political Advocacy; POLITICAL SCIENCE / Political Ideologies / Conservatism & Liberalism; Electronic books